Novel Mutations in COL6A3 That Associated With Peters’ Anomaly Caused Abnormal Intracellular Protein Retention and Decreased Cellular Resistance to Oxidative Stress - Li, Yue; Zhang, Jing; Dai, Yiqin; Fan, Yidan; Xu, Jianjiang (Frontiers in Cell and Developmental Biology, 2020)
Peters anomaly (PA) is a rare form of anterior segment dysgenesis characterized by central corneal opacity accompanied by iridocorneal or lenticulocorneal adhesions. Although genetic mutations, particularly those affecting transcription factors that function in eye development, are known to cause PA, the etiology of this disease remains poorly understood. In this study, 23 patients with PA were recruited for panel sequencing. Four out of 23 patients were found to carry variants in known PA causal genes, PITX2 and PITX3. More importantly, two homozygous mutations (NM_057164: p.Val86Ala and p.Arg689Cys) in the COL6A3 gene (collagen type VI alpha-3 chain) that correlated with the phenotype of type I PA were identified, and then validated by following whole-exome sequencing. The expression profile of the COL6A3 gene in the cornea and the mutations’ impacts on protein physiological processing and cellular function were further explored. It was shown that COL6A3 presented relatively high expression in the cornea. The mutant COL6A3 protein was relatively retained intracellularly, and its expression reduced cellular resistance to oxidative stress through an enhanced endoplasmic reticulum stress response. Taken together, our findings expanded the known genetic spectrum of PA, and provided evidence for the involvement of COL6A3 or collagen VI in ocular anterior segment development, thereby offering new insight for future investigations targeting PA.